From Online Learning to F2F: Learning Loss Still Remain or Even Learning Gain? - Mustaqim, Mujahidil; Pambudi, Pandu Dwi Luhur (FKIP Universitas Lampung, 2024)
From Online Learning to F2F: Learning Loss Still Remain or Even Learning Gain. Objectives: On June 21, 2023, the government of Indonesia issued a presidential decree (No. 17 of 2023) declaring the end of the country's outbreak of Covid-19. The restricted involvement in the educational process throughout the three-year period of the pandemic has led to considerable concerns regarding the existence of substantial academic deficiencies. The regulation signifies the conclusion of the pandemic's impact on online learning and the commencement of a return to traditional, in-person instruction. The objective of this study is to ascertain whether there has been a continued decline in academic performance or an improvement in learning outcomes since the pandemic Methods: The data were subjected to statistical analysis using regression and difference-in-differences techniques. This study was conducted with 720 high school students in Jakarta starting from the second wave of the pandemic in Indonesia and the first post-pandemic F2F period. Findings: The post-pandemic implementation of F2F demonstrated an improvement in learning outcomes across all three LS. However, the post-pandemic F2F transition also revealed unexpected contradiction in a small group of students. Conclusion: This highlights the need for further attention from educators and policymakers. Keywords: face to face learning, learning loss, learning gain, student learning styles, quality education.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024103